Answer:
The distance from p to l is ![\sqrt{10}\ units](https://tex.z-dn.net/?f=%5Csqrt%7B10%7D%5C%20units)
Step-by-step explanation:
we know that
The distance between point p from line l is equal to the perpendicular segment from line l to point p
step 1
<em>Find the slope of line l</em>
we have the points
(1,5) and (4, -4)
The formula to calculate the slope between two points is equal to
![m=\frac{y2-y1}{x2-x1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By2-y1%7D%7Bx2-x1%7D)
substitute the values
![m=\frac{-4-5}{4-1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-4-5%7D%7B4-1%7D)
![m=\frac{-9}{3}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-9%7D%7B3%7D)
![m=-3](https://tex.z-dn.net/?f=m%3D-3)
step 2
Find the equation of the line l
The equation in point slope form is equal to
![y-y1=m(x-x1)](https://tex.z-dn.net/?f=y-y1%3Dm%28x-x1%29)
we have
![m=-3](https://tex.z-dn.net/?f=m%3D-3)
![point\ (1,5)](https://tex.z-dn.net/?f=point%5C%20%281%2C5%29)
substitute
-----> equation A
step 3
Find the slope of the line perpendicular to the line l
Remember that
If two lines are perpendicular, then their slopes are opposite reciprocal (The product of their slopes is equal to -1)
![m_1*m_2=-1](https://tex.z-dn.net/?f=m_1%2Am_2%3D-1)
we have
---> slope of line l
therefore
----> slope of the line perpendicular to line l
step 4
Find the equation of the line perpendicular to line l that passes through the point p
The equation in point slope form is equal to
![y-y1=m(x-x1)](https://tex.z-dn.net/?f=y-y1%3Dm%28x-x1%29)
we have
![m=\frac{1}{3}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B1%7D%7B3%7D)
![point\ p(-1,1)](https://tex.z-dn.net/?f=point%5C%20p%28-1%2C1%29)
substitute
-----> equation B
step 5
Solve the system of equations
-----> equation A
-----> equation B
Solve the system by graphing
The solution of the system is the intersection point both graphs
The solution is the point q(2,2)
see the attached figure
step 6
we know that
The distance between the point p and the line l is equal to the distance between the point p and the point q
the formula to calculate the distance between two points is equal to
![d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28y2-y1%29%5E%7B2%7D%2B%28x2-x1%29%5E%7B2%7D%7D)
we have the points
p(-1,1) and q(2,2)
substitute the values
![d_p_q=\sqrt{(2-1)^{2}+(2+1)^{2}}](https://tex.z-dn.net/?f=d_p_q%3D%5Csqrt%7B%282-1%29%5E%7B2%7D%2B%282%2B1%29%5E%7B2%7D%7D)
![d_p_q=\sqrt{(1)^{2}+(3)^{2}}](https://tex.z-dn.net/?f=d_p_q%3D%5Csqrt%7B%281%29%5E%7B2%7D%2B%283%29%5E%7B2%7D%7D)
![d_p_q=\sqrt{10}\ units](https://tex.z-dn.net/?f=d_p_q%3D%5Csqrt%7B10%7D%5C%20units)